SOSIALISASI DAN INISIASI BADAN USAHA MILIK DESA (BUMDES) DESA MEJASEM BARAT KECAMATAN KRAMAT KABUPATEN TEGAL - agnes dwita susilawati; Budi Susetyo; Yuniarti Herwinarni; Mahben Jalil; Mei Rani Amalia (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
BUMDes is a form of strengthening village economic institutions and is a tool for utilizing the local economy, whose formation aims to improve the economic welfare of rural communities through the development of economic businesses and local sources of income. Its establishment is in line with Law No. 6 of 2004 concerning Villages and Permendes PDTT RI No. 4 of 2015. The purpose of this service activity is to find out the process of forming a good and professional West Mejasem Village BUMDes in accordance with its purpose. In this method of devotion there are 3 (three) stages; The first stage, socialization and initiation about the process of forming BUMDes, the second stage, participants get material "BUMDes", the third stage, participants get material on "The Meaning and Philosophy of BUMDes and Building the Profile and Character of Resilient Entrepreneurs". This counseling and role was held on Friday and Saturday, November 21, 2021, the opening of which was carried out by the Head of West Mejasem Village, Kramat District, Tegal Regency, which was attended by representatives from the District, Chairman of BKD, head of RW in the West Mejasem Village environment, Waste Management, and Karang Taruna. The implementation of the BUMDes SPIRIT Management Training program describes the strengthening of administration, especially accounting, marketing, and management in general. So that the expectation to be achieved is regarding the implementation of bookkeeping administration based on generally applicable rules, namely BUMDes Accounting by applying SAK ETAP.